NILAI-NILAI KARAKTER YANG DIKEMBANGKAN OLEH IBU RUMAH TANGGA DALAM MENJALANI TRADISI OTANG TENGKA - Riskiyah, Faridatur; Kholifah, Siti; Utaminingsih, Alifiulahtin (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
The significance of character values as shapers of the personality of the nation's golden generation can never be divorced from the actors involved as agents of socialization. This article seeks to explore the character values developed by housewives in the practice of the